COMPETITION AND QUALITY IN HOME HEALTH CARE MARKETS() - JUNG, KYOUNGRAE (2013)
Market-based solutions are often proposed to improve health care quality; yet evidence on the role of competition in quality in non-hospital settings is sparse. We examine the relationship between competition and quality in home health care. This market is different from other markets in that service delivery takes place in patients’ homes, which implies low costs of market entry and exit for agencies. We use 6 years of panel data for Medicare beneficiaries during the early 2000s. We identify the competition effect from within-market variation in competition over time. We analyze three quality measures: functional improvements, the number of home health visits, and discharges without hospitalization. We find that the relationship between competition and home health quality is nonlinear and its pattern differs by quality measure. Competition has positive effects on functional improvements and the number of visits in most ranges, but in the most competitive markets, functional outcomes and the number of visits slightly drop. Competition has a negative effect on discharges without hospitalization that is strongest in the most competitive markets. This finding is different from prior research on hospital markets and suggests that market-specific environments should be considered in developing polices to promote competition.